2017
DOI: 10.5817/sp2017-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Weaving the Threads of a Continuum: Teacher Education in Hungary from the Perspective of European Developments

Abstract: This paper aims to examine to what extent and how teacher education in Hungary reflects contemporary European policy and research developments with regard to the continuum of teacher education, meaning the overarching unity of initial teacher education, induction, and continuing professional development. First, the paper examines European policy documents to identify patterns and themes related to the continuum concept. Based on the specific analysis, a framework was developed to explore the continuum of teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Vilanova (2015) confirmed that the typical communication strategy of reforms is one of rupture. However, many investigations are carried out in order to understand the relevance (Lähdemäki, 2019;Wales et al, 2016) and the application (Berdugo & Montaño, 2017;Serbănescu, 2013;Symeonidis, 2017) of these policies, disregarding the discursive aspects that guide the policies themselves (Mejía-Cáceres et al, 2021), linking them to certain societal interests and projects. Perry et al (2010)…”
Section: Pre-service Education Of Teachers In Colombiamentioning
confidence: 99%
“…Vilanova (2015) confirmed that the typical communication strategy of reforms is one of rupture. However, many investigations are carried out in order to understand the relevance (Lähdemäki, 2019;Wales et al, 2016) and the application (Berdugo & Montaño, 2017;Serbănescu, 2013;Symeonidis, 2017) of these policies, disregarding the discursive aspects that guide the policies themselves (Mejía-Cáceres et al, 2021), linking them to certain societal interests and projects. Perry et al (2010)…”
Section: Pre-service Education Of Teachers In Colombiamentioning
confidence: 99%
“…Tensions were mainly caused by the redistribution of work time and resources, but, according to key policy players, the competence framework had little to do with it (Interview, NPE-6). When the new government revoked the Bologna structure and restored the undivided ITE programmes with Act CCIV of 2011 on National Higher Education following the demands of subject discipline lobbies (Symeonidis, 2017), little change took place with regard to the competence framework for ITE. The training and outcomes requirements (TORs) for ITE were only slightly modified in Annex 2 and Annex 3 of Government Decree 8/2013 which reduced the number of competences to eight instead of nine and introduced separate TORs for the subject disciplines.…”
Section: -2013: Teacher Competence Framework In the Context Of The Bo...mentioning
confidence: 99%
“…Another important implication of the new career model is that the qualification exam of novice teachers in the Intern stage, as well as the qualification process of Teacher although its components are based on international research results and global educational trends (e.g., becoming competence-based), the achievement of initial aims related to the increase of the teaching profession's prestige seems to be awaited. Moreover, despite the changes of several structural elements of teacher education, the prestige, the status of the profession is still relatively low (Symeonidis, 2018).…”
Section: Teacher Professionalism In Hungary In the Reflection Of Rece...mentioning
confidence: 99%